Development of Rock Teaching Media for Strengthening Students' Geoliteracy Skills in Geography Subjects - Akbar Maulana; Exsa Putra; Widyastuti Widyastuti; Ika Listiqowati (Universitas Sebelas Maret, 2025)
This study aims to develop learning media in the form of rock props on lithosphere material in Geography subjects. The method used is Research and Development (R&D) with reference to the Alessi and Trollip development model. Data analysis uses a Likert scale with four levels of validity. This research develops rock props media that can be used in geography learning lithosphere material. Then, a limited implementation was carried out by X social studies class students. The results showed that the rock props media developed had a very high level of validity. The validity assessment by media experts obtained a score of 91.66% with a very feasible category, by practitioners (teachers) of 97.61%, and by material experts of 90.27%, all included in the very valid category. Implementation of small group trials on students resulted in an average validity score of 91.73%, with a very valid category. In addition, the results of the student geoliteracy skills test showed an average percentage of 94.22%. Based on the assessment of experts, teachers and the results of student trials, the rock props media is declared feasible and effective to use in geography learning. Thus, this media is proven to be able to improve students' geoliteracy skills on lithosphere material at SMAN 1 Tojo.